Factors associated with post-election psychological distress: The case of the 2016 U.S. presidential election. (August 2018) - Pitcho-Prelorentzos, Shani; Kaniasty, Krzysztof; Hamama-Raz, Yaira; Goodwin, Robin; Ring, Lia; Ben-Ezra, Menachem; Mahat-Shamir, Michal
Highlights: Decision-making situations, such as democratic elections, are a cause of stress and in some cases may cause psychological distress This study examined factors associated with election-related psychological distress Psychological distress was positively associated with young age, consumption of new media, high political importance, political directness and voting for the candidate who did not win the elections. Abstract: This study, through the lens of Social Cognitive Theory, examined potential risk factors that may intensify election-related psychological distress. Six weeks after the 2016 U.S. election, 772 U.S. adult citizens filled out an online survey that assessed psychological distress along with sociodemographic characteristics, and a set of variables tapping various dimensions of political self-efficacy (i.e., importance of politics in one's life, preferences for different media outlets, political directness, and voting choices). The findings showed that election-related psychological distress was positively associated with young age, greater reliance on new media, greater importance of politics in one's life, higher political directness, and voting for the candidate who did not win the election. Findings should be valuable for health-care providers informing them about potential risk factors intensifying psychological distress in the context of significant political events.